Epistemic Justice as a Framework for Analyzing Early Grade Literacy Assessment Outcomes: A Baseline–Endline Analysis of the Balanced Reading Program in Badung Regency - Eka Yuliati; I Gede Ratnaya; Luhung Achmad Perguna; I Dewa Ayu Made Budhayani; I Gusti Lanang Parwata (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2026)
Reading assessment in early grades is commonly understood as a technical skill. However, the ability to make meaning from texts is a social practice also shaped by the mother tongue, culture, and pupils’ everyday experiences. This study aims to analyze changes in early-grade students’ literacy achievements after the implementation of the Balanced Reading Program in Badung Regency. In addition, the study examines cultural representation in the reading assessment instrument and discusses it from the perspectives of epistemic justice and cultural familiarity. The research uses a mixed-methods approach that combines quantitative analysis of baseline–endline data with qualitative document analysis of the assessment instrument. Quantitative data were obtained from baseline and endline tests without a control group. First- to third-grade pupils sampled at baseline numbered 320 and at endline 312. The sample was spread across six elementary schools. A total of 189 traceable paired data were analyzed using paired t-tests, Wilcoxon tests, Cohen’s d effect sizes, and rank-biserial correlations. The analysis shows statistically significant improvements in syllables (p < .001), nonword reading (p = .006), fluency (p = .017), and comprehension (p = .018), but with small to moderate effect sizes, so their practical significance should be interpreted proportionally. Letter-sound knowledge (p = .713) and listening (p = 1.000) tended to remain stagnant. Instrument review shows that, in general, the assessment texts are close to children’s world. However, the texts have not systematically integrated local languages, home literacy practices, and the socio-cultural landscape of Bali. These findings indicate potential problems of epistemic injustice in the design of reading assessments. Students may be evaluated using texts that do not necessarily provide equal opportunities to construct meaning. As conceptual implications and an agenda for further research, this study recommends developing reading assessments that are more culturally responsive.